2019
DOI: 10.1080/1331677x.2019.1638290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of terrorism on economic growth in Pakistan: an empirical analysis

Abstract: The paper examines the impact of terrorism on economic growth in Pakistan. Channel variables, such as foreign direct investment (FDI), domestic investment, and government spending, through which terrorism influences economic growth, are identified. For empirical analysis, annual data for the period 1972-2014 are used, and a structural model is estimated using the generalised method of moments (GMM) estimation approach. The results reveal that (1) the impact of terrorism on FDI and domestic investment is signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 54 publications
0
41
0
2
Order By: Relevance
“…Nurses of the current study identified financial constraints, lack of human resource, and deprived healthcare infrastructure as a major barrier while managing a terrorism-related disaster. Because of terrorism, Pakistan's economy has suffered a direct and indirect cost of almost US $126.79 billion ( 50 ). Local business and international trade are also adversely affected and resulted in increased inflation and loss of business market share.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses of the current study identified financial constraints, lack of human resource, and deprived healthcare infrastructure as a major barrier while managing a terrorism-related disaster. Because of terrorism, Pakistan's economy has suffered a direct and indirect cost of almost US $126.79 billion ( 50 ). Local business and international trade are also adversely affected and resulted in increased inflation and loss of business market share.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the absence of peace, these achievements are extremely fragile. Yet, a contrast can be found in Zakaria, Jun, and Ahmed (2019) who show that a 1% increase in terrorism reduces foreign direct investment (FDI) by 0.1%, and economic growth by 0.002%.…”
Section: Conceptualising a Costing Model For The Impact Of Terrorismmentioning
confidence: 99%
“…The Easter Sunday attack on 21 April 2019 severely impacted the tourism industry in Sri Lanka, and tourist arrivals dropped by more than 70 percent from a year earlier in May and approximately 60 percent in June. From the analysis based on annual data for the period of 1972-2014, Zakaria et al (2019) revealed that the terrorism impact on domestic investment is significantly negative, and a 1% increase in terrorism reduces domestic investment by 0.039 percent and economic growth by 0.002 percent in Pakistan. Further, Gaibulloev and Sandler (2008) revealed that an additional terrorist incident per million persons reduces GDP per capita growth by about 1.5% in Asian countries.…”
Section: International Terrorism and Religious Conflictsmentioning
confidence: 99%